Perancangan dan Pengembangan Sistem pada Beberapa Proyek di PT X - Olivia Justine Audia; Adelia Adelia (Journal of Smart Technology and Engineering, 2026)
This report discusses the implementation of an internship as a system analyst at PT X which is motivated by the company’s need for structured system analysis and documentation in the development of information systems across various projects. The purpose of this report is to explain the implementation of tasks, involvement in projects, and contributions made during the internship. The internship activities involved three system development projects, namely in a reinsurance company, a garment company, and a school. The methods used include observation and analysis of business processes, while data collection techniques consist of primary data obtained through direct involvement in projects and discussions with the team, as well as secondary data derived from internal company documents. The results of the internship activities include adding detailed information to specific sections of the Functional Specification Documents (FSD), preparing Minutes of Meeting (MoM) based on System Integration Testing (SIT) meetings, developing mapping documents and formula mappings, designing Business Process Model and Notation (BPMN), preparing FSD documents, and designing wireframes. The conclusion of this report indicates that the role of a system analyst plays an important contribution in bridging business needs with system development, while also providing practical experience in analysis, documentation, and project coordination processes in information system development across various client companies.